2010
DOI: 10.1182/blood-2010-03-275917
|View full text |Cite
|
Sign up to set email alerts
|

AIDS-related Burkitt lymphoma in the United States: what do age and CD4 lymphocyte patterns tell us about etiology and/or biology?

Abstract: Trimodal or bimodal age-specific incidence rates for Burkitt lymphoma (BL) were observed in the United States general population, but the role of immunosuppression could not be excluded. Incidence rates, rate ratios, and 95% confidence intervals for BL and other non-Hodgkin lymphoma (NHL), by age and CD4 lymphocyte count categories, were estimated using Poisson regression models using data from the United States HIV/AIDS Cancer Match study . BL incidence was 22 cases per 100 000 person-years and 586 for non-BL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(97 citation statements)
references
References 35 publications
3
91
0
3
Order By: Relevance
“…This association seems independent of the immune status, and HIV1 patients are at high risk of BL even with relatively high CD41 count. 23 Currently nearly 20% of BL diagnoses in the United States are in HIV1 patients. 11 Even though aggressive treatments are feasible in HIV1 patients, leading to results similar to the ones seen in the HIV2 population, 24,25 it is unknown if the lack of discrepancy in outcomes is due to patient selection.…”
Section: Discussionmentioning
confidence: 99%
“…This association seems independent of the immune status, and HIV1 patients are at high risk of BL even with relatively high CD41 count. 23 Currently nearly 20% of BL diagnoses in the United States are in HIV1 patients. 11 Even though aggressive treatments are feasible in HIV1 patients, leading to results similar to the ones seen in the HIV2 population, 24,25 it is unknown if the lack of discrepancy in outcomes is due to patient selection.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some GC-B cells also express the activation marker CD71 [27] and CD71 was identified as a non-immunoglobulin partner of BCL6 translocation, a common abnormality in NHL [28]. Finally, data by Guech-Ongey et al [29], suggested that in some AIDS-NHL cases malignant cells require functional CD4 lymphocytes to thrive. Supporting this finding, we determined a positive correlation between the frequency of the potentially malignant abnormal activated/GC-like B cells and CD4+ T cell count.…”
Section: Discussionmentioning
confidence: 99%
“…1 Rodent T-ALLs induced by a variety of genetic manipulations also exhibit frequent Notch1 mutations that render them Notch1-dependent for survival and proliferation in vitro. 1 Thus, aberrant Notch1 activation represents a key event in the multistep pathway of T-cell leukemogenesis in rodents and humans. Two articles in this issue report the unexpected finding that spontaneous or Cre-LoxP-targeted deletion of the 5Ј Notch1 promoter allows generation of leukemogenic Notch1 from "cryptic" internal promoters.…”
Section: Cynthia Guidos Hospital For Sick Children Research Institutementioning
confidence: 99%